Perspectives on New Testament Textual Criticism, Volume 2 : Collected Essays, 2006-2017 - Epp, Eldon Jay, (Novum Testamentum, Supplements ;, 2021)
Eldon Jay Epp's second volume of collected essays consists of articles previously published during 2006-2017. All treat aspects of the New Testament textual criticism, but focus on historical and methodological issues relevant to constructing the earliest attainable text of New Testament writings. More specific emphasis falls upon the nature of textual transmission and the text-critical process, and heavily on the criteria employed in establishing that earliest available text. Moreover, textual grouping is examined at length, and prominent is the current approach to textual variants not approved for the constructed text, for they have stories to tell regarding theological, ethical, and real-life issues as the early Christian churches sought to work out their own status, practices, and destiny.